2004
DOI: 10.1211/0022357023321
|View full text |Cite
|
Sign up to set email alerts
|

Melissa officinalis L. essential oil: antitumoral and antioxidant activities

Abstract: Melissa officinalis L (lemon balm) is a traditional herbal medicine used widely as a mild sedative, spasmolytic and antibacterial agent. This paper focuses on the analysis of the chemical composition and the biological activities of M. officinalis essential oil obtained under controlled harvesting and drying conditions. An in-vitro cytotoxicity assay using MTT indicated that this oil was very effective against a series of human cancer cell lines (A549, MCF-7, Caco-2, HL-60, K562) and a mouse cell line (B16F10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
115
0
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 25 publications
6
115
0
10
Order By: Relevance
“…Scientific studies have shown the role of essential oils in biological interactions among plants and their potential therapeutic including anti-inflammatory, analgesic, anti-tumor, antifungal, and antibacterial activities (Siani et al, 2000;Silva et al, 2003;Sousa et al, 2004;Osei-Safo et al, 2010;Kaileh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies have shown the role of essential oils in biological interactions among plants and their potential therapeutic including anti-inflammatory, analgesic, anti-tumor, antifungal, and antibacterial activities (Siani et al, 2000;Silva et al, 2003;Sousa et al, 2004;Osei-Safo et al, 2010;Kaileh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Melissa officinalis is an aromatic plant of the Lamiaceae family. Its EO presents different biological activities including an antitumor activity that was described by de Souza and colleagues [15]. In this work, it was shown that the essential oil of the plant could inhibit the viability of cell lines from various types of cancer such as breast, lung, colon, melanoma and leukemia.…”
Section: Essential Oilsmentioning
confidence: 68%
“…However, although these cells include a number chemo resistant lines like lung (A540) and melanoma (B16F10) the mechanism of their death was not investigated. The study of the composition of this EO, by gas chromatography, showed that it has as major components neral (39.28%) and geranial (47.32%), which together represent almost 90% of the oil composition [15]. These two compounds are isomers of the same molecule, citral.…”
Section: Essential Oilsmentioning
confidence: 97%
“…La Melissa officinalis posee un efecto antiviral (Dimitrova et al, 1993;Allahverdiyev et al, 2004), además de poseer propiedades antibacterianas y antimicóticas (Mimica-Dukic et al, 2004), evaluando su efecto antitumoral, debido a sus componentes antioxidantes (de Sousa et al, 2004), así como su capacidad sedante (Sadraei et al, 2003).…”
Section: Introductionunclassified